Nano hydrogels physico-chemical properties and recent advances in structural designing - Jose, Jiya; Thomas, Sabu 1960-; Thakur, Vijay Kumar 1981- (Gels horizons: from science to smart materials, 2021)
This book introduces the reader to important aspects of the nano-hydrogels. It covers the development of hydrogels and their biology, chemistry and properties. Focus is also given to innovative characterization techniques and advances in structural design, with special emphasis on molecular structure, dynamic behavior and structural modifications of hydrogels. This book serves as a consolidated reference work for the diverse aspects of hydrogels, creating a valuable resource for students and researchers in academia and industry